Effect of abandonment and plant classification on carbohydrate reserves of meadow plants - Janeček, S; Lanta, V; Klimešová, J; Doležal, J (Plant biology (Stuttgart, Germany), 2011)
We studied the effect of cessation of management on carbohydrate reserves of plants in meadows with different environmental characteristics and plant composition. We recorded storage carbohydrates and seasonal changes for 40 plant species. We asked whether there are differences in responses of carbohydrate reserves in forbs versus graminoids and in plants storing starch versus plants storing osmotically active carbohydrates. We analysed belowground organs before the meadows were mown and at the end of the vegetation season in mown versus recently abandoned plots. Whereas starch and fructans were widely distributed, raffinose family oligosaccharides were the main carbohydrate reserves of the Lamiaceae and Plantago lanceolata. Properties of carbohydrate reserves differed between forbs and graminoids but no difference was found between plants storing starch versus osmotically active carbohydrates. Graminoids had lower carbohydrate concentrations than forbs. We observed a positive effect of mowing on carbohydrate concentrations of graminoids in the dry, calcium-rich meadow and higher seasonal fluctuations of these values in the acid, wet meadow, suggesting that local factors and/or the species pool affect carbohydrate reserves. Despite local conditions, graminoids represent a distinct functional group in meadows from the point of view of their storage economy. We suggest that as well as growth, storage processes should also be considered for understanding the functioning of meadow plant communities.
Keywords: Česká republika; Lamiaceae; ekosystém; Czech Republic; roční období; škrob; Starch; sacharidy; Carbohydrates; hluchavkovité; půda; Plantago; Seasons; Ecosystem; Soil